2012
DOI: 10.2522/ptj.20100178
|View full text |Cite
|
Sign up to set email alerts
|

Using MeSH (Medical Subject Headings) to Enhance PubMed Search Strategies for Evidence-Based Practice in Physical Therapy

Abstract: Understanding how search terms map to MeSH terms and using the PubMed search strategy can enable physical therapists to take full advantage of available MeSH terms and should result in more-efficient and better-informed searches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 14 publications
0
39
0
3
Order By: Relevance
“…24 Similarly, Richter et al found that several entry terms commonly used by physical therapists did not map to an appropriate MeSH. 29 In the pharmacy field, an imbalance was found in MeSH coverage of pharmacy concepts relative to MeSH terminology specific to the nursing and dentistry professions. 9 Only 26 pharmacy-specific MeSH terms currently existing in the MeSH thesaurus were identified, as opposed to 94 and 145 nursing-and dentistry-specific, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…24 Similarly, Richter et al found that several entry terms commonly used by physical therapists did not map to an appropriate MeSH. 29 In the pharmacy field, an imbalance was found in MeSH coverage of pharmacy concepts relative to MeSH terminology specific to the nursing and dentistry professions. 9 Only 26 pharmacy-specific MeSH terms currently existing in the MeSH thesaurus were identified, as opposed to 94 and 145 nursing-and dentistry-specific, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The studies show that users perform searches with higher recall and precision if they make use of IRS search functions [35][36][37] . As such, it is important to make users aware about different help facilities offered by IRS.…”
Section: Help Facilitiesmentioning
confidence: 99%
“…No caso de fontes estruturadas por tesauro, como o PubMed/MedLine, a busca direta por termos indexados permite que se obtenha uma fração considerável do acervo do conhecimento para um projeto de pesquisa de maneira defensável e documentada (Richter & Austin, 2012). Entretanto, para quase todos os outros campos de conhecimento, não existem ainda bases que possuam tesauro e que sejam continuamente atualizadas para garantir a indexação das referências nos termos de um tesauro (Lipscomb, 2000).…”
Section: Processounclassified